Adiabatic sound transport in acoustic waveguides with time-varying Helmholtz resonators - Riva, Emanuele; Rosa, Matheus I. N.; Guo, Yuning; Ruzzene, Massimo (Frontiers in Acoustics, 2023)
We investigate the dynamics of acoustic waveguides with time-varying Helmholtz resonators and the ensuing wave propagation features. We focus on the numerical modeling of such a system with emphasis on the time-varying dispersion properties and emerging wave phenomena due to slow time modulation. We show that a propagating wave packet experiences a transformation that preserves the wavenumber content, resulting in frequency conversion that follows the time evolution of the dispersion bands. The conditions for such a transformation to be "adiabatic" are derived analytically, which allows the identification of the limiting modulation speed required to avoid undesired reflections or mode conversions. The predictions from the dispersion investigations are confirmed by time-domain numerical simulations, which illustrate the possibilities for frequency conversion and temporal signal compression or decompression of impinging signals. The framework presented herein may open new avenues in the context of time-varying phonic waveguides, with possible applications in communication, sound isolation, and frequency conversion.